Power-Generating Units of New Generation for Peak Mini-Power Complexes - S. V. Konstantinova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a load diagram leveling as of one of the means for higher operational efficiency of a power system and power saving. In order to reach the target it is supposed to use peak devices of the distributed generation (peak mini-power complexes) on the basis of cutting edge power equipment – micro-turbines of 30 kW–1MW capacity.